If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 229 = 14x + -14 Reorder the terms: 229 + 5x = 14x + -14 Reorder the terms: 229 + 5x = -14 + 14x Solving 229 + 5x = -14 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 229 + 5x + -14x = -14 + 14x + -14x Combine like terms: 5x + -14x = -9x 229 + -9x = -14 + 14x + -14x Combine like terms: 14x + -14x = 0 229 + -9x = -14 + 0 229 + -9x = -14 Add '-229' to each side of the equation. 229 + -229 + -9x = -14 + -229 Combine like terms: 229 + -229 = 0 0 + -9x = -14 + -229 -9x = -14 + -229 Combine like terms: -14 + -229 = -243 -9x = -243 Divide each side by '-9'. x = 27 Simplifying x = 27
| w^2-100w+2400=0 | | 152-4x=32x+20 | | 3x=6x-2 | | 8.2x-4.9x=-52.8 | | 4t+4(1-3t)= | | 1/9(4t-9)=t+9/18 | | (2x+5)(7x-1)= | | X-3(1-x)=47-y | | 6[3-(-4x-2)]=216x+126 | | 3d/2+5=8 | | 4/6c-4x+8/3=4/3 | | 0.20x+0.45(30)=21.5 | | 7y+2=3y+14 | | x^2+2x-783=0 | | 3x-3=6x+9 | | 5m+6=41 | | 4z-4.4=3.6 | | 2x+7/4=3x-7/4 | | 4(x+1)=2(x+7) | | 2x+1=3(x-1)-x+4 | | -(8x-6)= | | Y=21 | | -3(x-5)=-4x | | 53=3(y-2)-2(3y-1) | | 9(x-1)=6(x+2)-6 | | 63-x=x+3 | | (5b+3)(5b-8)= | | -x=x | | Sn=2n^2-8n | | 3k^2-17k+10=0 | | -13+2z=11 | | 5/8+3/4x=1/6 |